Mengelola Keseimbangan Hidup dan Pekerjaan: Dampak Burnout dan Peran Penting Kepuasan Kerja - Lutfiani, Maulita (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study aims to empirically test the mediating role of job satisfaction in the relationship between burnout and work-life balance (WLB). The research involved working students and alumni from three Jakarta-based institutions. The final analytical sample consisted of 103 respondents. Data were measured using a 5-point Likert scale, from the adaptation of validated measures. Mediation effects were tested using a bootstrapping methodology with the PROCESS V3.5 for SPSS 26. The results indicated that burnout has a significant negative effect on employee job satisfaction. Increases in employee job satisfaction will increase employee WLB perceptions. Furthermore, job satisfaction significantly mediated the negative relationship between burnout and WLB. The study provides practical implications for human resource management in developing strategies for burnout prevention and WLB promotion. Research limitations and suggestions for future research should be considered